Penggunaan Metode Make A Match Untuk Meningkatkan Hasil Belajar Siswa Pada Mata Pelajaran Tematik - Zainul Fuad (Awwaliyah: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2018)
The purpose of this research is to improve student learning outcomes on thematic subjects Theme 7 Events in the Life of Subtema 2 Events Nationality Regarding Proclamation Class V MI Al Fattah Sugihan Solokuro Lamongan Lesson 2017-2018. The type of research data used in this study is the type of data Qualitative and Quantitative research. The location of this research is MI Al Fattah Sugihan Solokuro Lamongan. The subject of this research is class V MI Al Fattah Sugihan Solokuro Lamongan Lessons Year 2017-2018 which amounted to 20 students. Techniques used in data collection is by interview techniques, observation, documentation, and test. Based on the analysis and discussion, it can be concluded that the use of make a match method can improve student learning outcomes of thematic subjects at MI Al Fattah Sugihan Solokuro Lamongan Lesson Year 2017-2018. This can be proved by the increase in learning outcomes for each cycle. In cycle I, the average score of student learning test result is 66,00 with percentage 45%. It is known by comparing the pre cycle value with the Cycle I value, the test result where the cycle value I is greater than the pre cycle of the mean value, that is: 66,00 > 58,25. While in cycle II, the average value of the test is 73.50 with a percentage of 75%. It is known by comparing the value of cycle I with Cycle II value, the test result where the value of cycle II is greater than the cycle I of the average value, namely: 73.50 > 66.00. And in cycle III, it can be seen that the average value of the test result is 81.00 with the percentage of 85%. It is known by comparing the value of cycle II with the value of Cycle III, the test results where the value of cycle III is greater than the cycle II of the average value, namely: 81.00 > 73.50. Based on the results of the study, it can be concluded that the use of make a match method can improve the students' learning outcomes of thematic subjects Theme 7 Events in the Life of Subtema 2 National Event About Proclamation Class V MI Al Fattah Sugihan Solokuro Lamongan Lesson 2017-2018.